The speech processing skills of children with cochlear implants - Pieterse-Randall, Candice (Stellenbosch : Stellenbosch University, 2008)
Thesis (MSL and HT (Interdisciplinary Health Sciences. Speech-Language and Hearing Therapy))--Stellenbosch University, 2008.